Mussels and Local Conditions Interact to Influence Microbial Communities in Mussel Beds - Higgins, Edward; Parr, Thomas B.; Vaughn, Caryn C. (Frontiers in Microbiology, 2022)
Microbiomes are increasingly recognized as widespread regulators of function from individual organism to ecosystem scales. However, how animals influence the structure and function of environmental microbiomes has received considerably less attention. Using a comparative field study, we investigated the relationship between freshwater mussel microbiomes and environmental microbiomes. We used two focal species of unionid mussels, Amblema plicata and Actinonaias ligamentina, with distinct behavioral and physiological characteristics. Mussel microbiomes, those of the shell and biodeposits, were less diverse than both surface and subsurface sediment microbiomes. Mussel abundance was a significant predictor of sediment microbial community composition, but mussel species richness was not. Our data suggest that local habitat conditions are a better predictor of environmental microbial community assemblages than spatial location along a river. Further, mussel burrowing activity and mussel shells may provide habitat for microbial communities critical to nutrient cycling in these systems.